Prevalence and Phage-Based Biocontrol of Methicillin-Resistant Staphylococcus aureus Isolated from Raw Milk of Cows with Subclinical Mastitis in Vietnam - Hoang Minh Son; Hoang Minh Duc (MDPI AG, 2024)
S. aureus, particularly methicillin-resistant S. aureus, has been recognized as a main cause of bovine mastitis and food poisoning. This study investigated the prevalence, antibiotic resistance, and phage-based biocontrol of S. aureus and methicillin-resistant S. aureus isolated from raw milk of cows with subclinical mastitis. The results showed that the prevalence of S. aureus and methicillin-resistant S. aureus was 12% (48/400) and 1.5% (6/400), respectively. The S. aureus isolates were highly resistant to penicillin (72.92%), erythromycin (43.75%), and tetracycline (39.58%). Out of 48 S. aureus isolates, 6 were identified as methicillin-resistant strains. Among them, one isolate was found to harbor the sea gene. A total of 5 phages were recovered from 50 pork and 50 chicken meat samples, 1 from pork and 4 from chicken meat samples. Phage PSA2 capable of lysing all 6 methicillin-resistant isolates was selected for characterization. The use of phage PSA2 completely inactivated methicillin-resistant S. aureus SA33 in raw milk at both 24 °C and 4 °C, indicating its potential as a promising antibacterial agent in controlling methicillin-resistant S. aureus in raw milk and treating bovine mastitis.